Synthesis and Analysis of Aluminium 6061 Composite Reinforced with Boron Carbide - R. Dhanraj; Dr. D. Balaji (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The synthesis and analysis of Aluminium 6061 composites reinforced with Boron Carbide (B4C) have been investigated to enhance the mechanical properties of the alloy. Aluminium 6061, known for its excellent mechanical properties and versatility, is further improved by incorporating Boron Carbide, a material renowned for its high hardness and wear resistance. The composites were synthesized using the stir casting process, with varying percentages of Boron Carbide reinforcement. The study focuses on evaluating the effects of Boron Carbide addition on the tensile strength, hardness, and impact strength of Aluminium 6061 composites. Experimental results show that the inclusion of Boron Carbide significantly improves the tensile and hardness properties of the composites. However, excessive reinforcement leads to increased brittleness, which can complicate machining processes. Through detailed laboratory experiments and analysis, the study provides insights into the optimal Boron Carbide content for balancing improved mechanical properties with practical manufacturing considerations. The findings highlight the potential of Aluminium 6061-Boron Carbide composites for applications requiring enhanced wear resistance and strength, while also addressing challenges related to brittleness and processing.